Legal gaps in indonesia's electronic information and transactions law in addressing deepfake technology: challenges and regulatory recommendations - Alzet Rama; Wiki Lofandri; Anggi Firmanjaya Saputra (SCHOULID: Indonesian Journal of School Counseling, 2025)
Deepfake technology, which leverages advanced artificial intelligence to create hyper-realistic manipulated media, has emerged as a significant legal and ethical challenge worldwide. In Indonesia, the rapid proliferation of deepfake content—ranging from political disinformation to non-consensual pornography—poses serious threats to privacy, reputation, and public trust. However, the existing Electronic Information and Transactions (ITE) Law does not explicitly regulate the creation, distribution, or malicious use of deepfake materials. This study employs a normative juridical approach combined with comparative legal analysis to examine the legal gaps within the ITE Law in addressing deepfake-related offenses. The research analyzes relevant case studies in Indonesia, evaluates the adequacy of current legal provisions, and compares Indonesia’s regulatory stance with that of jurisdictions such as the European Union, the United States, and Singapore. Findings reveal that the absence of specific legal definitions and enforcement mechanisms for deepfake content hinders effective law enforcement and victim protection. The study proposes concrete policy recommendations, including amendments to the ITE Law, the introduction of a comprehensive definition of deepfake technology, and the establishment of a multi-stakeholder oversight framework. These recommendations aim to strengthen Indonesia’s legal capacity to safeguard individual rights and uphold digital integrity in the era of AI-driven media manipulation